Digital Comics in Online Learning During COVID-19: Its Effect on Student Cognitive Learning Outcomes - Damopolii, Insar; Lumembang, Theresia; İlhan, Genç Osman (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Comics have been used as an alternative tool to improve student learning outcomes during the pandemic, but not yet for junior high school science learning. The study aims to explore the impact of digital comics in online learning during the COVID-19 pandemic on students' cognitive learning outcomes (CLO). A quasi-experimental research design was used in the study. A total of 42 eighth-grade students participated in the current study. They were randomly assigned to two conditions. The first condition was online learning assisted by digital comic media. The second condition was non-comic online learning. A multiple-choice test developed by the researchers was used to measure students' CLO. Although the number of participants is limited, an independent samples t-test was used to analyze the data because the data was normally distributed. The results show that students' CLO differs significantly between comic and non-comic assisted online learning in favor of comic assisted online learning conditions. The possible reasons behind the findings were discussed. As a conclusion, several suggestions for researchers and teachers were offered.